Transformasi Pembelajaran Pendidikan Agama Islam Melalui Pendekatan Humanistik: Menumbuhkan Kesadaran Beragama yang Holistik pada Siswa - Watawalaini, Ayu; Suryana, Ermis; Zulhijra, Zulhijra (FENOMENA, 2025)
Islamic Religious Education (PAI) learning is often delivered dogmatically so that it is less able to instill religious values deeply in students. This study aims to examine the application of the humanistic approach in Islamic Education learning to build a more holistic and meaningful understanding of religion. The method employed is a literature study with a conceptual analysis approach to humanistic education Theory, particularly the thoughts of Carl Rogers and other notable figures. The results of the study demonstrate that the humanistic approach, which emphasizes personal experience, reflection, empathy, dialogue, and active student participation, can enhance understanding and appreciation of Islamic values. Support from educators, educational institutions, and curriculum policies is necessary to implement this approach systematically.